Planning and organization of geriatric services : report of a WHO Expert Committee. - WHO Expert Committee on Planning and Organization of Geriatric Services (Geneva : World Health Organization, 1974)
Hoe organiseer je op een deftige manier de geriatrie?
Includes bibliographical references.
Keywords: Aged; Geriatrics; Health Planning; Health Services for the Aged; Older people; Older people